Geopolítica de los conceptos, servicios ecosistemáticos y bienes y servicios ambientales - Mora Vega, Roy (2013)
This paper makes a comparison of the emergence, development and implementation of the concepts of ecosystem services (SE) proposed by the Millennium Ecosystem Assessment(MEA) and Environmental Goods and Services (EGS), launched in the negotiations of the multilateral trading system in the World Trade Organization (WTO).